Pattern of caries lesions and oral health‐related quality of life throughout early childhood: A birth cohort study. (2nd August 2022) - Benelli, Kelly da Rocha Gomes; Chaffee, Benjamin W.; Kramer, Paulo Floriani; Knorst, Jessica Klöckner; Ardenghi, Thiago Machado; Feldens, Carlos Alberto
Abstract: The aim of this study was to evaluate the impact of different patterns of dental caries on oral health‐related quality of life (OHRQoL) throughout early childhood. This birth cohort study followed 277 children from southern Brazil for 6 years. Demographic and socioeconomic variables were collected at birth. At age 3 years, children's dental caries experience was quantified by the decayed, missing, or filled teeth (dmft) index. At age 6 years, parents answered the Early Childhood Oral Health Impact Scale (ECOHIS). Poisson regression models were used to estimate associations between caries experience and later OHRQoL, presented as the ratio of ECOHIS scores between the groups. The prevalence of dental caries at 3 years of age was 37.5%. In children with caries, lesions only in anterior teeth, only in posterior teeth, and in both dental segments at age 3 were associated with age 6 ECOHIS scores that were 2.7, 7.8, and 6.2 times higher, respectively, than in children without dental caries experience. OHRQoL was worse among children with higher dmft scores. Dental caries lesions in posterior teeth by age 3 years was strongly predictive of adverse impacts on later OHRQoL, presumably as an indicator of continued disease experience in the intervening years.